Realizing Gramsci’s Dream: A Case Study of Vernacular Sundanese Linguistic Contra-Hegemony - Wattimena, Sari (Advances in Social Sciences Research Journal, 2022)
The need to promote egalitarianism and reduce the colonial influence in language drives civil society actors and organizations operating within the community to revive their vernacular language, replacing hierarchical standard language exist in their community for a long time. Gramsci’s and Lu Xun’s efforts to promote vernacular language in Italy and China at their times faced failure. Today, in the democratic and digital-dominated society of Indonesia, the same effort has been taken by Aing Tangerang Foundation. This civil organization tries to revive egalitarian Sundanese language against hierarchical Sundanese brought by colonialism. One of their efforts is to popularize the word “Aing”, which means “I” in Sundanese conversation. The word is considered harsh by the majority of Sundanese using hierarchical standards. However, in Tangerang Regency, it is part of their mother tongue. This paper reports on a case study of the vernacular Sundanese linguistic revival campaign taken by the Aing Tangerang Foundation and strategies, drivers, and barriers they faced while promoting their cause. The data is collected through in-depth interviews with three informants: one expert in Sundanese literature, one expert in Sundanese history, and one is the leader of said organization. The research method is qualitative-phenomenological hermeneutics. We use Gramsci's hegemonic theory to analyze and discuss the findings. The results are presented and discussed related to horizontal and vertical strategies; political, organizational, and technological drivers; and historical, psychological, sociological, and sociofacts barriers.